A transferable interatomic potential for MgO from ab initio molecular dynamics - Aguado, A; Bernasconi, L; Madden, P (2002)
A refinement of the parameters appearing in the Aspherical Ion Model (AIM) potential is presented. The strategy involves fitting to the ab initio forces and stresses as obtained from the Density Functional Theory code CASTEP at ion configurations obtained from molecular dynamics runs at T = 1500 K and P = O GPa on a small system. The resulting potential is then shown to reproduce the experimental phonon dispersion curves at 300 K with a quality comparable to that of ab initio methods. The potential is also shown to predict thermal expansivities and isothermal compressibilities of MgO in excellent agreement with experimental results over the experimentally characterised range, demonstrating that the potential is transferable to (T,P) values far from those employed in the fitting. © 2002 Published by Elsevier Science B.V.